Assessing personality types preferences amongst software developers: A case of Malaysia - Omar, Mazni; Katuk, Norliza; Syed Abdullah, Sharifah Lailee; Hashim, Nor Laily; Romli, Rohaida (Asian Research Publishing Network (ARPN), 2015)
This paper aims to present personality types preferences among software developers in Northern region of Malaysia.Knowledge in human factor personality types is significant in order to assist project manager for making decision on the right personality types that suit into job tasks assigned to software developers.In addition, there is growing awareness on applying agile methodology during software development.This software methodology claimed to be acknowledged human weaknesses and strengths and thus, has great potential in improving software development effectiveness.Therefore, this study also seeks to compare personality type’s preferences amongst agile and non-agile software developers.A questionnaire that includes personality test questions was distributed amongst 81 software developers that working in the software industry. Results demonstrated that the software developers are mostly Introvert (I) personality types. Furthermore, the dimensions of Intuitive (N), Thinking (T), and Judging (J) are dominant personality types among software developers regardless of software methodology used. This study provides an insight into personality type’s preferences that can guide human resource manager to select the suitable candidate for specific tasks in order to improve team performance.Future studies will be carried out to collect more empirical data and to build software team personality types composition model.